Chemical composition of submicron and fine particulate matter collected in Krakow, Poland. Consequences for the APARIC project. (November 2017) - Samek, Lucyna; Furman, Leszek; Mikrut, Magdalena; Regiel-Futyra, Anna; Macyk, Wojciech; Stochel, Grażyna; van Eldik, Rudi
Abstract: Submicron particulate matter containing particles with an aerodynamic diameter ≤1 μm (PM1) are not monitored continuously by Environmental Protection Agencies around the World and are seldom studied. Numerous studies have indicated that people exposed to ultrafine (≤100 nm), submicron and fine particulate matter containing particles with an aerodynamic diameter ≤2.5 μm (PM2.5), can suffer from respiratory track diseases, cardiovascular, immunological or heart diseases and others. Inorganic pollutants containing redox active transition metals and small gaseous molecules, are involved in the generation of reactive oxygen and reactive nitrogen species. Inhalation of this kind of particles can affect immune-toxicity. Environmental pollution may aggravate the course of autoimmune diseases, in particular influence the mechanisms of the autoimmune system. Important factors that influence the toxicity of particulate matter, are particle size distribution, composition and concentration. This report deals with the composition of PM1 and PM2.5 fractions collected in Krakow, Poland. In spring 2015, the mean concentrations of PM1 and PM2.5 were 19 ± 14 and 27 ± 19 μg/m 3, respectively. The PM2.5 fraction contained approximately 70 ± 17% of submicron particulate matter. In spring 2016, the mean concentrations of PM1 and PM2.5 were 12 ± 5 and 22 ± 12 μg/m 3, respectively. The PM2.5 fraction contained approximately 60 ± 15% of submicron particulate matter. The concentrations of the elements Cl, K, Ca, Ti, Cr, Mn, Fe, Ni, Cu, Zn, Br, Rb, Sr and Pb in both fractions were determined by X-ray fluorescence spectrometry. Most of the analyzed metals had higher concentrations in the fine fraction than in the submicron one. Concentrations of V and As were below the detection limit in both fractions, whereas concentrations of Mn and Ca were below the detection limits in the PM1 fraction. The results are discussed in terms of the consequences they may have on the APARIC project presently underway in Krakow. Graphical abstract: Highlights: Krakow is a highly polluted city with serious environmental health problems. Patients in Krakow suffer from respiratory track, cardiovascular and immunological diseases. The composition of PM1 and PM2.5 fractions collected in Krakow was determined. A large fraction of submicron PM was found that could have important health consequences.